PENGARUH DISIPLIN TERHADAP EFEKTIFITAS KERJA KARYAWAN PT. MITRA ANIM HA SEJAHTERA MERAUKE - Elisabeth Pruwo Gebze (EKONOMI & SOSIAL, 2018)
Study aims to determine the effect of discipline on the work effectiveness of employees of PT. Mitra Anim Merauke Prosperous Justice. The sample in this study were 33 respondents, the sampling method used was the technique of total sampling and sampling was done using a Likert Scale, then the data was processed using SPPS version 20 with a simple linear regression analysis technique. From the regression analysis obtained by the equation Y = 2,588 + 0,784 (X). Hypothesis testing using the t test shows that the discipline variable (X) is proven to have a significant effect on work effectiveness, this is evidenced by the value of t count, (X) = 0.784 with a significant level of 0,000 <0.05 so ha is accepted and h0 is rejected. R Square number of 57.1% shows that work effectiveness can be explained by disciplinary variables, while 42.9% is explained by other variables not examined in this study.